Factors Influencing Tourism English Vocabulary Learning and Strategy Use Among Third-Year English-Major Students: A Qualitative Case Study at Thanh Do University - Duc Quy Nguyen; Tuan Vuong Minh; Nghia Nguyen Trong; Thuy Nguyen Thi Minh; Hung Giang Phu (An-Nasyi'in: Jurnal Ilmu Pendidikan, 2026)
Tourism English vocabulary plays an important role in preparing English-major students for future careers in the tourism industry. However, learning specialized vocabulary can be challenging due to its complexity and limited use in everyday communication. This study aimed to investigate the factors influencing tourism English vocabulary learning and the vocabulary learning strategies used by third-year English-major students at Thanh Do University, Vietnam. A qualitative case-study approach was employed. Data were collected from eleven students through written reflections and semi-structured interviews and analyzed using thematic analysis. The findings revealed five major factors affecting vocabulary learning: career-oriented motivation, complex nature of tourism vocabulary, teacher-guided learning and classroom activities, access to learning resources and technology, and lack of authentic practice opportunities. Four main learning strategies were identified: memory-based learning, contextual and communicative learning, technology-mediated learning, and multimedia-based learning. The findings contribute to a better understanding of tourism vocabulary learning and provide implications for improving vocabulary instruction in higher education.